1986
DOI: 10.1007/bf02382072
|View full text |Cite
|
Sign up to set email alerts
|

A new procedure to study the perceptual world of animals with sensory reinforcement: Recognition of humans by a chimpanzee

Abstract: ABSTRACT. A female chimpanzee touched a button to produce colored slides of pictures. Slides were present as long as she kept touching the button. Repeated touch within 10 sec after the previous release produced the same slides again. The slide was changed when 10 sec passed after she released the button. The duration of a touching response and the interval between the responses were calculated for each of 100 slides. The data for each slide were plotted on the two-dimensional space constructed with response d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 12 publications
2
33
0
Order By: Relevance
“…During sessions, the left lever was always lighted except while the rotary magazine was rotated. This procedure was identical to that employed by FUJITA and MATSUZAWA (1986). The majority of the subjects (those with an asterisk in Table 1) were not allowed to see the same picture continuously for more than 10 sec.…”
Section: Methodsmentioning
confidence: 99%
“…During sessions, the left lever was always lighted except while the rotary magazine was rotated. This procedure was identical to that employed by FUJITA and MATSUZAWA (1986). The majority of the subjects (those with an asterisk in Table 1) were not allowed to see the same picture continuously for more than 10 sec.…”
Section: Methodsmentioning
confidence: 99%
“…Chimpanzees have been shown to demonstrate remarkable cognitive capabilities that are often strikingly reminiscent ofhuman reasoning abilities and conceptual skills (see, e.g., Boysen, Berntson, Shreyer, & Hannan, 1995;Fujita & Matsuzawa, 1986;Gillan, Premack, & Woodruff, 1981;Matsuzawa, 1985aMatsuzawa, , 1985bPremack, 1986;Savage-Rumbaugh, 1986). For example, they have been shown to have impressive capabilities in numerical processing, symbolic representation ofnumber, and even numerical reasoning that does not require the support of language, as typically defined (see, e.g., Boysen, 1997;, Boysen & Berntson, 1989Matsuzawa, 1985b;Murofushi, 1997).…”
Section: Sarah T Boysen Kimberly L Mukobi and Gary G Berntsonmentioning
confidence: 99%
“…Also, SWARTZ (1980) found that long-tailed macaques display different viewing durations depending on the macaques species presented. FUJITA and MATSUZAWA (1986) showed that a chimpanzee exhibited longer viewing duration towards human slides than towards non-human slides.…”
Section: Introductionmentioning
confidence: 98%